Cutaneous Manifestations of Cobalamin Deficiency in Bowel Resection Patient with Thalassemia Trait - Mekasuwandit, Patchareya; Laodheerasiri, Supapat (Thai Journal of Dermatology, 2024)
A 32-year-old male patient with a history of ileum dissection due to blunt abdominal injury, a history of bacterial overgrowth, and beta thalassemia traits, presented with hyperpigmentation at palms, gingivae, nails, and premature greying of hair. His hematologic conditions included megaloblastic anemia. Peripheral blood smear revealed hypersegmented neutrophils. The bone marrow biopsy showed neucleocytoplasmic asynchrony. Neurological examination was completed without significant finding of proprioception loss or ataxia. The cobalamin level was confirmed as low level. One mg of B12 was intramuscularly injected daily for a week and 1 mg intramuscular injection weekly. One month following, the hair showed repigmentation.